ОБ ОДНОЗНАЧНОЙ РАЗРЕШИМОСТИ ОБОБЩЕННОЙ ЗАДАЧИ КОЛЕБАНИЯ БАЛКИ - Реймбаева, Д.К. (SCIENCE and SOCIETY, 2024)
The paper proves the theorem of the existence and uniqueness of the solution of the problem in Sobolev classes. The solution of the problem under consideration is constructed as the sum of a series according to the system of eigenfunctions of a multidimensional spectral problem.